CO2‐Responsive "Smart" Single‐Walled Carbon Nanotubes. (7th November 2012) - Guo, Zanru; Feng, Yujun; He, Shuai; Qu, Meizhen; Chen, Honglin; Liu, Hanbin; Wu, Yufeng; Wang, Yu
<x xml:space="preserve">Abstract</x> A new type of "smart" single‐walled carbon nanotubes is created by wrapping a pyrene‐labeled CO2‐responsive polymer via π–π stacking. The polymer/SWNT hybrids not only undergo a hydrophobic–hydrophilic transition upon CO2 stimulus of CO2 in a mixed solvent, but also exhibit switchable dispersion/aggregation states upon the alternate bubbling of CO2 and N2 in pure water. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>